The Criminogenic effects of economic and demographic characteristics in Canada - Chew, Lee Ping (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study examines the relationships between crimes and their economic and demographic determinants in Canada. Cointegration and causality analyses have been canied out in this study for the sample period of 1971 to 2009. The results of cointegration analysis indicate that there is a cointegrated vector between the variables used for total crime and homicide, but no long-mn relationship existed between motor vehicle theft and economic and demographic variables. Granger causality tests show that total crime and homicide are affected by unemployment rate, real gross domestic product (GDP), proportion of population aged 15-24, and fertility rate in the long-run. Besides that, unemployment rate, proportion of population aged 15-24 and fe11ility rate Granger cause total crime whereas the proportion of population aged 15-24 Granger causes fertility rate in the short-mn. There is no short-mn causality existed between motor vehicle theft and the economic and demographic variables used in Canada.